Petrochemical characteristics of late Paleozoic magmatic rocks of the Mandakh area, southeast Mongolia (Mongolian Geoscientist, 2018)
The late Paleozoic magmatic rocks are widely distributed in the Mandakh area which is located in the Gurvansaikhan and Manlai terrains, where porphyry Cu deposits occur. In this paper we discuss petrochemical features and mineral assemblages of magmatic rocks in the Mandakh area. Furthermore, we compared petrochemical characteristics of magmatic rocks in the Mandakh area with host magmatic rocks of the Tampakan deposit (Philippines), Cerro Colorado deposit (Chili) and negative criteria of Cu deposits (Japan) due to try to characterize potential of the porphyry copper deposit related to magmatic rocks in Mandakh area. Geochemical features of magmatic rocks in Mandakh area are calc-alkaline, magnetite-series, I-type and similar to adakite type. The Devonian intrusive rocks comprised of syenite and syenogranite, while the Carboniferous intrusive rocks consist of granodiorite, monzodiorite, quartz-monzonite and hornblende granite. Devonian magmatic rocks are more alkaline in composition. Although, Devonian and Carboniferous magmatic rocks are slightly different from each other. Comparing with bonanza copper deposits in the world, they are possible to host porphyry mineralization.